Direct evidence on risk attitudes and migration - David A. Jaeger (Institute for the Study of Labor (IZA), 2007)
Geographic mobility is important for the functioning of labor markets because it brings labor resources to where they can be most efficiently used. It has long been hypothesized that individuals' migration propensities depend on their attitudes towards risk, but the empirical evidence, to the extent that it exists, has been indirect. In this paper, we use newly available data from the German Socio-Economic Panel to measure directly the relationship between migration propensities and attitudes towards risk. We find that individuals who are more willing to take risks are more likely to migrate between labor markets in Germany. This result is robust to stratifying by age, sex, education, national origin, and a variety of other demographic characteristics, as well as to the level of aggregation used to define geographic mobility. The effect is substantial relative to the unconditional migration propensity and compared to the conventional determinants of migration. We also find that being more willing to take risks is more important for the extensive than for the intensive margin of migration
urn:nbn:de:101:1-2008041665
Keywords: 330; Regionale Arbeitsmobilität; Binnenwanderung; Risikopräferenz; Deutschland